Humidity effect on electrochemical performance of Li–O2 batteries - Guo, Ziyang; Dong, Xiaoli; Yuan, Shouyi; Wang, Yonggang; Xia, Yongyao (Journal of power sources, 2014)
In this work, we compare the performance of Li–O2 batteries in pure/dry O2, pure O2 with a relative humidity (RH) of 15% and ambient air with an RH of 50%, and analyze the ambient humidity effect on the reactions in the carbon-based catalytic electrode. Electrochemical investigation indicates that discharge capacities of Li–O2 batteries increased with growth of RH value, but cyclic ability and rate performance are influenced in an opposite way. Ex-situ X-ray diffraction (XRD), Fourier transform-infrared spectrophotometer (FT-IR) and scanning electron microscope (SEM) investigations suggest that ambient humidity affects not only the Li2O2/O2 conversion, LiCO3/CO2 conversion and LiOH formation but also the morphology of discharge products in porous catalytic electrode over charge/discharge cycle. These results may be important for developing Li–air battery. •Humidity is a strong capacity enhancer for the Li–O2 batteries, but limits the cyclic ability and rate performance.•Humidity affects the Li2O2/O2 conversion, LiCO3/CO2 conversion and LiOH formation over charge/discharge cycle.•Humidity varying results in different morphologies of the discharge products.